Prevalence of ESBL in Escherichia coli Isolates Among ICU Patients in a Tertiary Care Hospital - Nipa Singh; Dipti Pattnaik; Dhruba Kumar Neogi; Jagadananda Jena; Bandana Mallick (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Resistance to common antibiotics is a matter of grave concern in treating infections in hospital settings especially in Intensive Care Units (ICUs). One of the most commonly used and effective group of antibiotics, cephalosporins, exhibit resistance due to production of Extended Spectrum BetaLactamases (ESBLs). The prevalence of ESBL producing Escherichia coli (E.coli) has increased throughout the world and is a major cause of treatment failure in ICUs. As per our knowledge studies were not available on the prevalence of ESBL producing E.coli in ICUs of this region. Aim: To determine the prevalence of ESBLs among Escherichia coli isolates in ICUs of a tertiary care hospital. Materials and Methods: A cross sectional study was conducted over a period of 4 years (Sept 2011 to Sept 2015) in the Department of Microbiology, Kalinga Institute of Medical Sciences (KIMS), Bhubaneswar. Consecutive non-duplicate isolates of E.coli recovered from 6800 clinical samples of patients admitted to different Intensive Care Units (ICUs) were subjected to ESBL screening test and then to CLSI recommended Phenotypic Confirmatory Disc Diffusion Tests (PCDDT) for ESBL production determination. Results: Out of 6800 samples, 1038 were E.coli isolates and 452(44%) were resistant to third generation cephalosporins. ESBL producing Escherichia coli among them were 276 (61.1%). Paediatric ICU showed the highest prevalence of ESBL E.coli at 80.9%. The highest prevalence of ESBL E.coli was in urine samples (82.6%) followed by pus (9.8%). The most effective antibiotic for ESBL producers was imipenem (96.7% sensitive), followed by amikacin (88.4%) and piperacillin- tazobactum (87%). Conclusion: This study has highlighted the high prevalence of ESBL producing E.coli in the ICUs of our hospital. An in depth analysis of their antibiogram will be helpful in formulating the antibiotic policy and prevent spread of ESBL strains. It is recommended that ESBL testing should be done routinely to curtail antibiotic resistance and to effectively implement infection control measures.